Nurses Shift Handover Instrument Development Evaluation Using SBAR Effective Communication Method - Purwanza, Sena Wahyu; Fitryasari, Rizki; Rahayu, Puji (International Journal of Psychosocial Rehabilitation, 2020)
Effective communication of SBAR is a method used in patient handover performed by nurses. Communication made on patient handover by nurses is vulnerable to failure. The study aimed to develop a nurse handover shift instrument accordance to the standards. Design of this research was an explorative descriptive research with a research and development approach. The population was medical record documents in inpatient unit of Haji General Hospital Surabaya. The sample was 167 medical record documents obtained by purposive sampling based on inclusion criteria. This variable was a nurse shift handover instrument consisting of the situation, background, assessment, recommendations. Researchers used the handover checklist form as instrument. The data were then analyzed using descriptive statistically and followed by focus group discussion to develop the new instrument. The results show there were 84% incomplete components of the situation, 100% incomplete of background, 100% incomplete of assessment and 100% incomplete of recommendations. The incomplete documents are caused by the lacking of nurse’s knowledge and understanding of the function of the handover instrument, duplication of documentation, differences in medical and nursing diagnoses for each patient, ineffectiveness of socialization and dissemination of instrument filling guidelines. It is necessary to revise the nurse handover shift instrument with an effective SBAR communication approach in accordance with hospital accreditation standards, so as to prevent patient safety incidents and improve the quality of nursing services.